Nothing to lose: a J.P. Beaumont novel (J. P. Beaumont mysteries, 25, 1, 2022)
Years ago, when he was a homicide detective with the Seattle PD, J.P. Beaumont's partner, Sue Danielson, was murdered. Volatile and angry, Danielson's ex-husband came after her in her home and, with nowhere else to turn, Jared, Sue's teenage son, frantically called Beau for help. Now, almost twenty years later, Jared reappears in Beau's life seeking his help once again - his younger brother Chris is missing. Following a lead all the way to the wilds of wintertime Alaska, he encounters a tangled web of family secrets in which a killer with nothing to lose is waiting to take another life.
J. A. Jance.

An anonymous girl (Thorndike Press, a part of Gale, a Cengage Company, St. Martin's Press, A Macmillan Audiobook from St. Martin's Press, Macmillan Audio, 2019)
"When Jessica Farris signs up for a psychology study conducted by the mysterious Dr. Shields, she thinks all she'll have to do is answer a few questions, collect her money, and leave. But as the questions grow more and more intense and invasive and the sessions become outings where Jess is told what to wear and how to act, she begins to feel as though Dr. Shields may know what she's thinking...and what she's hiding."--

Girl, forgotten: a novel (Andrea Oliver novels, 2, 1, 2023)
Forty years after Emily Vaughn was murdered on her prom night, U.S. Marshal Andrea Oliver picks up the cold case to find justice. Who killed Emily Vaughn? The stunning new standalone thriller from international No. 1 bestseller Karin Slaughter. A girl with a secret ... Longbill Beach, 1982. Emily Vaughn gets ready for prom night, the highlight of any high school experience. But Emily has a secret. And by the end of the evening, she will be dead. A murder that remains a mystery ... Forty years later, Emily's murder remains unsolved. Her friends closed ranks, her family retreated inwards, the community moved on. But all that's about to change. One final chance to uncover a killer ... Andrea Oliver arrives in town with a simple assignment: to protect a judge receiving death threats. But her assignment is a cover. Because, in reality, Andrea is here to find justice for Emily - and to uncover the truth before the killer decides to silence her too.

Last day (Thomas & Mercer, Brilliance Audio, Center Point Large Print, 2021)
"Years ago, Beth Lathrop and her sister Kate suffered what they thought would be the worst tragedy of their lives the night both the famous painting Moonlight and their mother were taken. The detective assigned to the case, Conor Reid, swore to protect the sisters from then on. Beth moved on, throwing herself fully into the art world, running the family gallery, and raising a beautiful daughter with her husband Pete. Kate, instead, retreated into herself and took to the skies as a pilot, always on the run. When Beth is found strangled in her home, and Moonlight goes missing again, Detective Reid can’t help but feel a sense of déjà vu. Reid immediately suspects Beth’s husband, whose affair is a poorly kept secret. He has an airtight alibi—but he also has a motive, and the evidence seems to point to him. Kate and Reid, along with the sisters’ closest childhood friends, struggle to make sense of Beth’s death, but they only find more questions: Who else would have wanted Beth dead? What’s the significance of Moonlight? Twenty years ago, Reid vowed to protect Beth and Kate—and he’s failed. Now solving the case is turning into an obsession." --book jacket

The hunt: a Decker/Lazarus novel (Peter Decker and Rina Lazarus mysteries, 27, 1, 2022)
Peter and his partner, Detective Tyler McAdams, are thrown into an unsolved case and propelled into action when a body is found in the very woods where a man previously went missing in upstate New York. But that's not the only crisis that Peter has to deal with. Teresa McLaughlin, the biological mother of Peter and his wife Rina's foster son, Gabe, has fled to Los Angeles with her two children in tow, hoping to avoid a court injunction amid a messy divorce. But LA is no escape from her problems--she is found by ruthless men and beaten mercilessly. When she wakes, barely conscious, Teresa discovers that both of her children are gone and frantically calls Gabe for help. With his mother on the verge of death, Gabe contacts Peter and Rina, as well as his biological father, the notorious Christopher Donatti, a former hit man from a known criminal family who's now a millionaire in Nevada. By bringing Donatti into the fray, Gabe, Peter, and Rina know they have made a deal with the devil--but they may not be able to recover the kids without him. As these unlikely allies rally to find the kidnappers before things end tragically, they race headlong toward an explosive confrontation from which no one will emerge unscathed...
Faye Kellerman.

A justified murder (Medlar mysteries, 2, 1, 2019)
"The small town of Lachlan, Florida, was rocked last year when two bodies were uncovered in the roots of a fallen tree. Despite their lack of investigative experience, Sara Medlar; her niece, Kate; and Jack Wyatt found themselves at the center of the mystery, working together to reveal the truth behind a decades-old secret in the sleepy town. After a narrow escape, they vowed to never again involve themselves in something so dangerous--until Janet Beeson is murdered. When Janet's body is discovered, everyone is shocked by the violence of the attack. The sweet little old woman has been shot, stabbed and poisoned, but no one can imagine who would want to harm one of the town's kindest, most helpful residents. Sara, Kate and Jack are determined to leave this case to the professionals. But they are soon bombarded by townspeople eager to tell their stories and clear their names with the trio who solved the Morris murders. Even the sheriff is hoping they'll lend their skills to a crime that seems to have no explanation and no motive. And once the town gets talking, they begin to see that there are more secrets buried in quiet Lachlan than anyone could have imagined"--

The cage: a novel (HarperCollins, HarperAudio, Harper, an imprint of HarperCollinsPublishers, Harper, 2022)
On a cold, misty Sunday night, two women are alone in the offices of fashion conglomerate Claudine de Martineau International. One is the company's human resources director. Impeccably dressed and perfectly coiffed, she sits at her desk and stares somberly out the window. Down the hall, her colleague, one of the company's lawyers, is buried under a pile of paperwork, frantically rushing to finish. Leaving at the same time, the two women, each preoccupied by her own thoughts, enter the elevator that will take them down from the 30th floor. When they arrive at the lobby, one of the women is dead. Was it murder or suicide?

The black echo (Harry Bosch mysteries, 1, 1, 2012)
For maverick LAPD homicide detective Harry Bosch, the body in the drainpipe at Mulholland Dam is more than another anonymous statistic. This one is personal . . . because the murdered man was a fellow Vietnam "tunnel rat" who had fought side by side with him in a hellish underground war. Now Bosch is about to relive the horror of Nam. From a dangerous maze of blind alleys to a daring criminal heist beneath the city, his survival instincts will once again be tested to their limit. Pitted against enemies inside his own department and forced to make the agonizing choice between justice and vengeance, Bosch goes on the hunt for a killer whose true face will shock him.
The very first Harry Bosch novel, winner of the Edgar Award for Best First Novel, is available once more. A body discovered in a drainpipe on Mulholland Drive turns out to be a fellow Vietnam "tunnel rat" who had fought by the side of the maverick LAPD homicide detective. Now Bosch is about to relive the horror of 'Nam while on the hunt for a killer whose true face will shock him.

Manhunt: a Michael Bennett story (Bookshots, , 1, 2017)
"Michael Bennett, be grateful you're alive. Someone attacked the Thanksgiving Day Parade directly in front of Michael Bennet and his family. The television news called it 'holiday terror'; Michael Bennett calls it personal. The hunt is on...."--Back cover.

The wrong victim (Quinn & Costa, 3, 1, 2022)
"A bomb explodes on a sunset charter cruise out of Friday Harbor at the height of tourist season and kills everyone on board. Now this fishing and boating community is in shock and asking who would commit such a heinous crime--the largest act of mass murder in the history of the San Juan Islands. Forensic profilers know there are two types of domestic terrorists: those who use violence to instill fear for political purposes but stop at murder because it detracts from the cause, and those who crave attention and are willing to maim and murder for their own agenda. Accused of putting profits before people after leaking fuel that caused a massive fish kill, the West End Charter company may itself have been the target. But as special agent Matt Costa, detective Kara Quinn and the rest of the FBI team begin their investigation, they discover that plenty of people might have wanted someone dead on that yacht. Now they must track down who is responsible and stop them before they strike again"--

The drowned girl (Louise Rick/Camilla Lind, ,, 2018)
It's clearly no ordinary drowning. When a young girl is pulled from the watery depths, a piece of concrete tied around her waist and two mysterious circular patches on the back of her neck, Detective Louise Rick is immediately called out to Holbraek Fjord. Her name was Samra, and Louise soon learns that her short life was a difficult one, as part of Copenhagen's sizeable Muslim immigrant community. Samra's father had already been charged once with assaulting her, and her mother is sure he would be capable of killing anyone who brought dishonor to the family. Yet Samra, she insists, had done nothing dishonorable. So was her death really an honor killing, or something even more sinister? Navigating the complex web of family and community ties in Copenhagen's tightly knit ethnic communities, Louise must hunt a killer before he strikes again ...